The Genome Sequence of Mycoplasma mycoides subsp. mycoides SC Type Strain PG1(T), the Causative Agent of Contagious Bovine Pleuropneumonia (CBPP) - Westberg, Joakim (Cold Spring Harbor Laboratory Press, 2004)
Mycoplasma mycoides subsp. mycoidesSC (MmymySC)is the etiological agent of contagious bovine pleuropneumonia (CBPP), a highly contagious respiratory disease in cattle. The genome of Mmymy SC type strain PG1(T) has been sequenced to map all the genes and to facilitate further studies regarding the cell function of the organism and CBPP. The genome is characterized by a single circular chromosome of 1,211,703 bp with the lowest G+C content (24 mole%)and the highest density of insertion sequences (13% of the genome size)of all sequenced bacterial genomes. The genome contains 985 putative genes, of which 72 are part of insertion sequences and encode transposases. Anomalies in the GC-skew pattern and the presence of large repetitive sequences indicate a high genomic plasticity. A variety of potential virulence factors was identified, including genes encoding putative variable surface proteins and enzymes and transport proteins responsible for the production of hydrogen peroxide and the capsule, which is believed to have toxic effects on the animal.